THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON THE COMPANY'S FINANCIAL PERFORMANCE - Devi Wulandari, Amalia; Rozzi Rahmawati, Septiana; Hwihanus, Hwihanus (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The underlying premise of this research underscores that Corporate Social Responsibility (CSR) initiatives can yield advantageous outcomes for companies, encompassing legitimacy and favorable societal reception. This study aims to examine the influence of CSR on corporate financial performance, synthesizing findings from investigations in Pakistan, China, Tanzania, Bangladesh, and Taiwan. Consistent findings across these studies affirm a positive correlation between CSR activities and firm performance. Employing Meta Analysis methodology, the study evaluates CSR's impact on financial performance, affirming through theoretical synthesis and empirical evidence a robust positive association between CSR engagement and financial outcomes. The study's specific findings indicate that although CSR's immediate financial impact may be modest, it accrues substantial fiscal benefits over the long term.